2017
DOI: 10.1038/s41598-017-09262-6
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin1, a novel regulator of pronephros development, influences retinoic acid and Wnt signaling by controlling ROS levels

Abstract: Peroxiredoxin1 (Prdx1) is an antioxidant enzyme belonging to the peroxiredoxin family of proteins. Prdx1 catalyzes the reduction of H2O2 and alkyl hydroperoxide and plays an important role in different biological processes. Prdx1 also participates in various age-related diseases and cancers. In this study, we investigated the role of Prdx1 in pronephros development during embryogenesis. Prdx1 knockdown markedly inhibited proximal tubule formation in the pronephros and significantly increased the cellular level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 45 publications
(55 reference statements)
1
11
1
Order By: Relevance
“…However, multiple mechanisms have been proposed to explain Prdx1's effects on cilia depolymerization. Chae Soomin et al(44) found that Prdx1 knockdown markedly inhibited proximal tubule formation in the pronephros during embryogenesis, significantly increased the cellular levels of reactive oxygen species (ROS), and impaired primary cilia formation, findings that do not agree with our observations. The difference in activities may reflect different roles of Prdx1 in cilia formation for different cellular components and different disease conditions.…”
contrasting
confidence: 99%
“…However, multiple mechanisms have been proposed to explain Prdx1's effects on cilia depolymerization. Chae Soomin et al(44) found that Prdx1 knockdown markedly inhibited proximal tubule formation in the pronephros during embryogenesis, significantly increased the cellular levels of reactive oxygen species (ROS), and impaired primary cilia formation, findings that do not agree with our observations. The difference in activities may reflect different roles of Prdx1 in cilia formation for different cellular components and different disease conditions.…”
contrasting
confidence: 99%
“…However, multiple mechanisms have been proposed to explain Prdx1's effects on cilia depolymerization. Chae Soomin et al [44] found that Prdx1 knockdown (See figure on previous page.) Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Prdxs denote the family of proteins having the ability to efficiently scavenge peroxides in the form of hydrogen peroxide, alkyl hydro peroxide, and peroxynitrite [33]. Prdxs are classified into six subfamilies, according to PeroxiRedoxin classification index (PREX) and, in mammals, there are six Prdxs, among which Prdx 1–4 belongs to Prdx1 subfamily, Prdx5 is a member of Prdx5 subfamily, and Prdx6 represent Prdx6 subfamily [34,35]. Prdxs are also classified as 1-Cys containing only Prdx6, while typical 2-Cys comprised of Prdx1–4 and Prdx5 belongs to atypical 2-Cys on the basis of their cysteine residues and their catalytic mechanism [36].…”
Section: Mitochondrial Prdxsmentioning
confidence: 99%
“…Both mitochondrial Prdxs comprise peroxidatic cysteine (Cp) and resolving cysteine (Cr) which play an essential role in their catalytic mechanisms. In Prdx3, Cp is located at residue 47, whereas, in Prdx5, it is located at residue 48 [35].…”
Section: Figurementioning
confidence: 99%